Paraharmotrema karinganiense n. gen., n. sp. (Digenea: Liolopidae) infecting the intestine of serrated hinged terrapin (Pelusios sinuatus), east African black mud turtle (Pelusios subniger), and South African helmeted turtle (Pelomedusa galeata) and a phylogenetic hypothesis for liolopid genera. (April 2022) - Dutton, Haley R.; DuPreez, Louis H.; Urabe, Misako; Bullard, Stephen A.
Abstract: We herein describe Paraharmotrema karinganiense n. gen., n. sp. Dutton & Bullard (Liolopidae Dollfus, 1934) from specimens infecting the intestine of the serrated hinged terrapin ( Pelusios sinuatus ), east African black mud turtle ( Pelusios subniger ) (both Nwanedzi River, Mozambique), and South African helmeted terrapin ( Pelomedusa galeata ) (North-western Zululand, KwaZulu-Natal Province, South Africa). The new genus can be easily differentiated from the other accepted liolopid genera ( Liolope Cohn, 1902; Helicotrema Odhner, 1912; Harmotrema Nicoll, 1914; Dracovermis Brooks & Overstreet, 1978) by the combination of having a linguliform body approximately 6–9 × longer than wide, tegumental spines/scales, a minute ventral sucker located in the anterior 1/7−1/8 of the body, deeply lobed testes that are transverse and abut the caeca (spanning the intercaecal space), a uterus that is lateral to the anterior testis (not ventral to the anterior testis), a lobed ovary that is dextral and nearest the posterior testis, and a vitellarium that does not extend anteriad to the level of the ventral sucker and that does not fill the intercaecal space. Nucleotide sequences of large subunit ribosomal DNA ( 28S ) and internal transcribed space region ( ITS2 ) from all analyzed specimens of the new species were identical, respectively; the 28S sequences differed from that of Liolope copulans Cohn, 1902 and from that of Harmotrema laticaudae Yamaguti, 1933 by 103 (8%) and 105 (8%) nucleotides, respectively. The 28S phylogenetic analysis recovered the new genus sister to a clade comprising L. copulans and H. laticaudae . A key to liolopid genera is provided herein. The present study comprises the first nucleotide-based phylogenetic placement of Harmotrema and first record of a liolopid from South Africa or Mozambique. It is the first proposal of a new liolopid genus in 43 yrs, and it documents a second liolopid genus from P. subniger while tripling the number of liolopid turtle hosts reported from the continent of Africa. Graphical abstract: Image 1 Highlights: Description of  Paraharmotrema karinganiense  n. gen., n. sp. Dutton & Bullard (Liolopidae Dollfus, 1934) from African turtles. First nucleotide-based phylogenetic placement of Harmotrema and first record of a liolopid from South Africa or Mozambique. Documents a second liolopid genus from P. subniger . Triples the number of liolopid turtle hosts reported from the continent of Africa. Comments on Brooks and Overstreet 1978.